PEMBERDAYAAN KELEMBAGAAN KORPORASI KARANG TARUNA DESA BANTARSARI MELALUI BADAN HUKUM KOPERASI SERBA USAHA DAN PENGUATAN PARTISIPASI - Purwaningsih, Endang; Yusuf, Chandra; Bakry, Mohammad Ryan; Ramadhan, Muhammad Satrio; Nugraha, Farel Fathin (Universitas Mataram, 2025)
This Community Engagement Program responds to the need for strengthening youth-based economic institutions in Bantarsari Village, Rancabungur District, Bogor Regency. Karang Taruna, the village youth organization, had not yet established a legally recognized business entity to support its collective economic activities. Key issues included the absence of a formal cooperative institution, low youth participation in village economic structures, and limited managerial and legal understanding of business operations. This program aimed to enhance the knowledge, motivation, and participation of Karang Taruna members in forming and managing a multi-purpose cooperative. The methods employed consisted of interactive lectures, participatory training, focused group discussions, pre- and post-assessment tests, and legal documentation assistance, resulting in the issuance of a notarial deed, Ministry approval (SK AHU), and Business Identification Number (NIB). The outcomes demonstrate a significant improvement in the individual and organizational capacity of Karang Taruna, culminating in the establishment of a legally recognized cooperative as a participatory and adaptive institution to support youth-driven economic development in the village.